Whole knee joint T1 values measured in vivo at 3T by combined 3D ultrashort echo time cones actual flip angle and variable flip angle methods. Issue 3 (16th November 2018) - Ma, Ya‐Jun; Zhao, Wei; Wan, Lidi; Guo, Tan; Searleman, Adam; Jang, Hyungseok; Chang, Eric Y.; Du, Jiang
Abstract : Purpose: To measure T1 relaxations for the major tissues in whole knee joints on a clinical 3T scanner. Methods: The 3D UTE‐Cones actual flip angle imaging (AFI) method was used to map the transmission radiofrequency field (B1 ) in both short and long T2 tissues, which was then used to correct the 3D UTE‐Cones variable flip angle (VFA) fitting to generate accurate T1 maps. Numerical simulation was carried out to investigate the accuracy of T1 measurement for a range of T2 values, excitation pulse durations, and B1 errors. Then, the 3D UTE‐Cones AFI‐VFA method was applied to healthy volunteers ( N = 16) to quantify the T1 of knee tissues including cartilage, meniscus, quadriceps tendon, patellar tendon, anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), marrow, and muscles at 3T. Results: Numerical simulation showed that the 3D UTE‐Cones AFI‐VFA technique can provide accurate T1 measurements (error <1%) when the tissue T2 is longer than 1 ms and a 150 μs excitation RF pulse is used and therefore is suitable for most knee joint tissues. The proposed 3D UTE‐Cones AFI‐VFA method showed an average T1 of 1098 ± 67 ms for cartilage, 833 ± 47 ms for meniscus, 800 ± 66 ms for quadriceps tendon, 656 ± 43 ms for patellar tendon, 873 ± 38 ms for ACL, 832 ± 49 ms for PCL, 379 ± 18 ms for marrow, and 1393 ± 46 ms for muscles. Conclusion: The 3D UTE‐Cones AFI‐VFA method allows volumetric T1 measurement of the major tissues in whole knee joints on a clinical 3T scanner.